Impact of Practice-Based Management of Pulmonary Artery Pressures in 2000 Patients Implanted With the CardioMEMS Sensor. Issue 16 (18th April 2017) - Heywood, J. Thomas; Jermyn, Rita; Shavelle, David; Abraham, William T.; Bhimaraj, Arvind; Bhatt, Kunjan; Sheikh, Fareed; Eichorn, Eric; Lamba, Sumant; Bharmi, Rupinder; Agarwal, Rahul; Kumar, Charisma; et al.
Abstract : Background: Elevated pulmonary artery (PA) pressures in patients with heart failure are associated with a high risk for hospitalization and mortality. Recent clinical trial evidence demonstrated a direct relationship between lowering remotely monitored PA pressures and heart failure hospitalization risk reduction with a novel implantable PA pressure monitoring system (CardioMEMS HF System, St. Jude Medical). This study examines PA pressure changes in the first 2000 US patients implanted in general practice use. Methods: Deidentified data from the remote monitoring Merlin.net (St. Jude Medical) database were used to examine PA pressure trends from the first consecutive 2000 patients with at least 6 months of follow-up. Changes in PA pressures were evaluated with an area under the curve methodology to estimate the total sum increase or decrease in pressures (mm Hg-day) during the follow-up period relative to the baseline pressure. As a reference, the PA pressure trends were compared with the historic CHAMPION clinical trial (CardioMEMS Heart Sensor Allows Monitoring of Pressure to Improve Outcomes in New York Heart Association [NYHA] Functional Class III Heart Failure Patients). The area under the curve results are presented as mean±2 SE, and P values comparing the area under the curve of the general-use cohort with outcomes in the CHAMPION trial were computed by the t test with equal variance. Results: Patients were on average 70±12 years old; 60% were male; 34% had preserved ejection fraction; and patients were followed up for an average of 333±125 days. At implantation, the mean PA pressure for the general-use patients was 34.9±10.2 mm Hg compared with 31.3±10.9 mm Hg for CHAMPION treatment and 32.0±10.5 mm Hg for CHAMPION control groups. The general-use patients had an area under the curve of −32.8 mm Hg-day at the 1-month time mark, −156.2 mm Hg-day at the 3-month time mark, and −434.0 mm Hg-day after 6 months of hemodynamic guided care, which was significantly lower than the treatment group in the CHAMPION trial. Patients consistently transmitted pressure information with a median of 1.27 days between transmissions after 6 months. Conclusions: The first 2000 general-use patients managed with hemodynamic-guided heart failure care had higher PA pressures at baseline and experienced greater reduction in PA pressure over time compared with the pivotal CHAMPION clinical trial. These data demonstrate that general use of implantable hemodynamic technology in a nontrial setting leads to significant lowering of PA pressures.